Innovative Chemistry Learning: The Impact of the Jigsaw Cooperative Model on Students’ Understanding of Reaction Rate Concepts - Mareta Dwi Astuti (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to determine the effect of the Jigsaw type cooperative learning model on students' chemistry learning outcomes on the concept of reaction rate by comparing it with the expository learning method at the high school level. Methodology: Quasi-experimental method, Only Posttest Control Group Design, purposive sampling technique, multiple-choice test instrument (22 questions), validity and reliability test using ANATES software, Liliefors normality test, Fisher homogeneity test, and t-test statistical analysis at a significance level of α = 0.05. Main Findings: The average value of the experimental group (70.15) was higher than the control group (57.87). The results of the statistical test showed that tcount = 4.47 was greater than ttable = 1.999, so there was a significant difference. The Jigsaw Model was proven to improve student learning outcomes on the concept of reaction rate. Novelty/Originality of this study: This research focuses on the application of the Jigsaw model to the under-researched concept of reaction rate. This study provides empirical evidence of its effectiveness in chemistry learning and enriches innovative learning strategies to enhance conceptual understanding and student engagement.